CRF-R1 Antagonist Treatment Exacerbates Circadian Corticosterone Secretion under Chronic Stress, but Preserves HPA Feedback Sensitivity - Yadira Ibarguen-Vargas; Samuel Leman; Rupert Palme; Catherine Belzung; Alexandre Surget (MDPI AG, 2021)
Despite promising initial reports, corticotropin-releasing factor receptor type-1 (CRF-R1) antagonists have mostly failed to display efficacy in clinical trials for anxiety or depression. Rather than broad-spectrum antidepressant/anxiolytic-like drugs, they may represent an 'antistress' solution for single stressful situations or for patients with chronic stress conditions. However, the impact of prolonged CRF-R1 antagonist treatments on the hypothalamic-pituitary-adrenal (HPA) axis under chronic stress conditions remained to be characterized. Hence, our study investigated whether a chronic CRF-R1 antagonist (crinecerfont, formerly known as SSR125543, 20 mg·kg−1·day−1 ip, 5 weeks) would alter HPA axis basal circadian activity and negative feedback sensitivity in mice exposed to either control or chronic stress conditions (unpredictable chronic mild stress, UCMS, 7 weeks), through measures of fecal corticosterone metabolites, plasma corticosterone, and dexamethasone suppression test. Despite preserving HPA axis parameters in control non-stressed mice, the 5-week crinercerfont treatment improved the negative feedback sensitivity in chronically stressed mice, but paradoxically exacerbated their basal corticosterone secretion nearly all along the circadian cycle. The capacity of chronic CRF-R1 antagonists to improve the HPA negative feedback in UCMS argues in favor of a potential therapeutic benefit against stress-related conditions. However, the treatment-related overactivation of HPA circadian activity in UCMS raise questions about possible physiological outcomes with long-standing treatments under ongoing chronic stress.